Pengaruh Organizational Culture dan Quality Of Work Life terhadap Motivasi Kerja Guru Madrasah Ibtidaiyah - Muhamad Suhardi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the influence of Organizational Culture and Quality of Work Life on the Work Motivation of Madrasah Ibtidaiyah (MI) teachers, Gunung Sari District, West Lombok Regency, for the 2021/2022 Academic Year. This research is a quantitative study in madrasas organized under the Ministry of Religion, Gunung Sari District, West Lombok Regency, West Nusa Tenggara. This study uses a survey method with path analysis applied in hypothesis testing. The study was conducted on 179 teachers as respondents who were selected at simple random. The results of this study are: (1). There is a positive direct influence of organizational culture (Organizational Culture) on work motivation. (2). There is a positive direct influence on the quality of work life (Quality of Work Life) on work motivation, and (3). There is a direct positive influence of organizational culture (Organizational Culture) on the quality of work life (Quality of Work Life). Keywords: organizational culture, work motivation, quality of work life.